Stellar disk evolution and gaseous disk turbulence of dwarf irregular galaxies : doctoral thesis accepted by University of Chinese Academy of Sciences, Beijing, China /: doctoral thesis accepted by University of Chinese Academy of Sciences, Beijing, China. ([2016]) - Zhang, Hong-Xin
No abstract available